Environmental Burden of Diseases - Utama, Winda Trijayanthi (Fakultas Kedokteran, 2019)
The Environmental Burden of Diseases (EBD) study assesses the Health Impact Assessment (HIA), the burden of disease caused by an environmental risk factor, and is closely related to the assessment of disease burden for individual disease and injury. In practice this is the result of an environmental health impact assessment. Data on disease burden and injury, which have been assessed at a global level, can be used for the EBD study. The results of the EBD study are generally presented in the form of gender and age groups, and are measured for mortality as well as public health measurement units such as DALYs (Disability-Adjusted Life Year).Keywords: Disability-Adjusted Life Year, Environmental Burden of Diseases, Health Impact AssessmentKorespondensi: dr. WInda Trijayanthi U, SH., M.K.K; Fakultas Kedokteran Universitas Lampung